2021
DOI: 10.1021/acs.analchem.1c02322
|View full text |Cite
|
Sign up to set email alerts
|

Sortase-Mediated Phage Decoration for Analytical Applications

Abstract: Phage-borne peptides and antibody fragments isolated from phage display libraries have proven to be versatile and valuable reagents for immunoassay development. Due to the lack of convenient and mild-condition methods for the labeling of the phage particles, isolated peptide/protein affinity ligands are commonly removed from the viral particles and conjugated to protein tracers or nanoparticles for analytical use. This abolishes the advantage of isolating ready-to-use affinity binders and creates the risk of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The direct insertion of foreign genes facilitates 100% display of the endogenous peptide on M13 surface, but only within short peptide. With the assistance of transpeptidase, for instance, Sortase A, the size of peptide/protein displayed on M13 surface can be facilely expanded [25,105,106]. However, Sortase A-based displaying strategy faced another issue of reaction reversibility [107].…”
Section: Remaining Issues and Future Perspectivesmentioning
confidence: 99%
“…The direct insertion of foreign genes facilitates 100% display of the endogenous peptide on M13 surface, but only within short peptide. With the assistance of transpeptidase, for instance, Sortase A, the size of peptide/protein displayed on M13 surface can be facilely expanded [25,105,106]. However, Sortase A-based displaying strategy faced another issue of reaction reversibility [107].…”
Section: Remaining Issues and Future Perspectivesmentioning
confidence: 99%
“…After testing, it was found that each phage can be coupled with up to 102 ± 16 Nluc molecules, and the Nluc-labeled dual display phage was employed to develop a phage bioluminescent immunoassay (P-BLEIA) for the detection of herbicide 2,4-D, which represent a 16-fold improvement compared to the phage enzyme-linked immunosorbent assay (ELISA). 24 However, the traditional multivalent PAEC development strategies are cumbersome and time consuming, which limits its application in immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al optimized the phage display system to produce M13 phage particles that express the nanobody on pIII and a polyglycine short peptide (LPETGG) fused to pVIII that allows the covalent attachment of nanoluciferase (Nluc) employing sortase A. Aer testing, it was found that each phage can be coupled with up to 102 ± 16 Nluc molecules, and the Nluc-labeled dual display phage was employed to develop a phage bioluminescent immunoassay (P-BLEIA) for the detection of herbicide 2,4-D, which represent a 16-fold improvement compared to the phage enzyme-linked immunosorbent assay (ELISA). 24 However, the traditional multivalent PAEC development strategies are cumbersome and time consuming, which limits its application in immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 Compared with conventional IgG antibodies, nanobodies, which have determine genetic code, exhibit unique advantages, such as great antigenicity toward cryptic epitope, high thermostability, simple expression system, and ease of genetic engineering, and facilitate the construction of immunoassays. 13−15 At present, nanobody-based immunoassays have found extensive application in diverse analytical domains, including the analysis of mycotoxins, 16−18 pesticide residues, 19 foodborne pathogens, 20,13 environmental pollutants, 21,22 and cancer markers. 23,24 However, their diminutive size poses a challenge as passive adsorption of nanobodies onto physical surfaces in a random manner can significantly compromise their binding function.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, nanobodies derived from the heavy chain antibodies of camelids and cartilaginous fish have emerged as a subject of increasing interest in the realm of immunoassays. Compared with conventional IgG antibodies, nanobodies, which have determine genetic code, exhibit unique advantages, such as great antigenicity toward cryptic epitope, high thermostability, simple expression system, and ease of genetic engineering, and facilitate the construction of immunoassays. At present, nanobody-based immunoassays have found extensive application in diverse analytical domains, including the analysis of mycotoxins, pesticide residues, foodborne pathogens, , environmental pollutants, , and cancer markers. , However, their diminutive size poses a challenge as passive adsorption of nanobodies onto physical surfaces in a random manner can significantly compromise their binding function. This arises from the fact that their binding interface constitutes a relatively larger proportion of the total surface area, leading to concealed binding sites and a diminished signal-to-noise ratio, particularly when detecting large molecules like bacteria and proteins .…”
Section: Introductionmentioning
confidence: 99%